Early Versus Usual Palliative Care Consultation in the Intensive Care Unit. (May 2023) - Helgeson, Scott A.; Burnside, Rebecca C.; Robinson, Maisha T.; Mack, Rachel C.; Ball, Colleen T.; Guru, Pramod K.; Moss, John E.
Objectives: Palliative Medicine involvement in MICU patients have improved length of stay and mortality, but with varying effects on specific patient decision outcomes, such as, advance care planning. These studies have utilized Palliative Medicine later in the hospital or ICU course, with some evidence showing that earlier involvement resulted in better results. The purpose of this study was to evaluate the benefits of early (within 24 hours) palliative care consultation in medical ICU (MICU) patients to clinical and satisfaction outcomes. Methods: An unblinded randomized study performed in the MICU in one academic hospital in the USA. Ninety-one adult patients admitted to MICU received a Palliative care medicine consultation within 24 hours as the intervention. Measurements and results: Ninety-one patients admitted to the MICU underwent randomization with 50 patients randomly assigned to receive Palliative Medicine consultation and 41 patients randomly assigned to receive standard-of-care based on predefined criteria. The median satisfaction score was 23 points higher for the patients in the intervention group (P < .001). The median length of MICU stay was 5 days shorter in the intervention group compared to the control group (95% CI; 1 day to 18 days, P = .018). Advance care planning was completed in the hospital for 34% of patients in the intervention arm and 12% of patients in the controls arm (absolute risk difference 22%, 95% CI 4% to 37%, P = .016). Conclusion: Early Palliative Medicine consultation within 24 hours of MICU admission showed significant benefits to patients by improving satisfaction and decreasing length of stay. This study provides evidence that Palliative Medicine involvement earlier in the course of severe disease is important. Further studies in other types of intensive care units (neurological and Cardiovascular) are necessary to determine their impact.